PENDEKATAN SAINTIFIK DENGAN MODEL PEMBELAJARAN NUMBER HEAD TOGETHER DAPAT MENINGKATKAN HASIL BELAJAR ROLL BELAKANG - Suryani Suryani; Resky Ana Abadi; Fitriani Fitriani; Ika Sartika; Basman Basman; Edy Gunawan (Indonesian Journal Of Physical Activity and Sport Development (IJPASD), 2023)
This class action research aims to determine the level of student learning outcomes through a scientific approach with the Number Head Together learning model in grade IV students of SDN 81 Kendari, in the even semester of the 2021/2022 academic year consisting of 20 students. The research was carried out in two cycles with four stages: planning, implementation, observation, and reflection. Data collection of learning outcomes using Attitude Observation, Student Worksheets, and Back Roll Ability Tests. Data analysis was carried out in accordance with standard Benchmark Reference Approach (PAP) 5 and statistical calculations. The results of the study showed that students who completed learning in the first cycle were only 30%. And in cycle II, students who completed learning as much as 85%. The results of the analysis also showed that there was a significant increase in learning outcomes of the back roll technique in grade IV students of SDN 81 Kendari. It can be concluded that the implementation of a scientific approach with the Number Head Together learning model can improve student learning outcomes.